2021
DOI: 10.1097/corr.0000000000002024
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Probability of Reporting Various Levels of Pain 12 Months After Noncatastrophic Injuries Associated with the Level of Peritraumatic Distress?

Abstract: BackgroundPsychological factors have been shown to be consistent predictors of chronic pain in people with musculoskeletal injuries. However, few prognostic studies have considered multiple risk factors including peritraumatic distress. In addition, previous research has not considered that the associations between peritraumatic distress and pain levels can vary across pain outcomes.Question/purposeTo determine whether an easily measurable level of baseline distress is associated with pain levels 1 year after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…Still, such studies need to use prospective, randomized, or at least cohort designs to see the true effect. Modarresi et al [6] showed that this can be done in a relatively small number of patients. Increasing awareness of the physical, emotional, and societal costs of open tibia fractures will lead to increased funding for research to investigate the psychosocial component for recovery from injury and surgery.…”
Section: How Do We Get There?mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, such studies need to use prospective, randomized, or at least cohort designs to see the true effect. Modarresi et al [6] showed that this can be done in a relatively small number of patients. Increasing awareness of the physical, emotional, and societal costs of open tibia fractures will lead to increased funding for research to investigate the psychosocial component for recovery from injury and surgery.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The average interview time was 53 minutes. To be more practical for orthopaedic surgeons with limited time available in clinic, we need a fast and reliable screening tool for identifying patients who have less than ideal coping strategies in order to help find them resources [6]. As indicated in the paper, resources available online were very helpful for patients since they're readily available to patients with internet access.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…One of the main barriers of screening for psychological factors like depression, anxiety, catastrophic beliefs about pain, and heightened levels of distress is that most orthopaedic surgeons feel as though such work is beyond their expertise. A recent study published in CORR [5] described a new scale, the Traumatic Injuries Distress Scale (TIDS), which predicted pain-related outcomes after acute musculoskeletal injuries. The TIDS questionnaire takes patients less than 3 minutes to complete, and the authors found that it reliably anticipated which patients who presented with noncatastrophic orthopaedic injuries were more likely still to have pain a year later [5].…”
mentioning
confidence: 99%
“…A recent study published in CORR [5] described a new scale, the Traumatic Injuries Distress Scale (TIDS), which predicted pain-related outcomes after acute musculoskeletal injuries. The TIDS questionnaire takes patients less than 3 minutes to complete, and the authors found that it reliably anticipated which patients who presented with noncatastrophic orthopaedic injuries were more likely still to have pain a year later [5]. Importantly, the TIDS questionnaire focuses on patients' self-perceived relationships to pain, as well as issues of affect, intrusive thoughts, and hyperarousal [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation